Risk factors in childrenwith platelet refractoriness - Jonliberti Purba; Sri Mulatsih; Neti Nurani; Teguh Triyono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Platelet transfusions are often performed in pediatric patients. Nevertheless, platelet transfusion has its own risk and it alsoincrease the cost of care. Therefore,its effectiveness needs to be evaluated. This study aimed to assess the clinical risk factors namely sepsis, splenomegaly, DIC, severe bleeding and the history of platelet transfusion in the incidence of refractory platelets. This was a case-control study conducted during the period of August 2010 to September 2011.From a total of 1403 cases of transfusion, there were 86 incidences of refractory and 86 of nonrefractory. From the bivariate analysis, it was obtained that sepsis [OR 5.91 (2.90-12.05)], p = 0.000], splenomegaly [OR 2.82 (1.32-6.04.12), p = 0006] heavy bleeding [OR 8:41 (4.19-16.871), p = 0.000 ], DIC [OR 22.96 (6.73-78.35), p = 0.000] and the history of platelet transfusions [OR 5:33 (2.78-10.23), p = 0.000] increase the risk of refractory platelets. On multivariate analysis, sepsis (OR 2.96 [95% CI: 1:19 to 7:32], p = 0019), splenomegaly (OR 3.94 [95% CI: 2:21 to 16:00], p = 0.000), severe bleeding (OR 3:53 [95% CI : 1.40-8.89], p = 0.008), DIC (5:54 OR [95% CI: 1.29-22.75], p = 0021) and platelet transfusion the history (OR 2.84 [95% CI: 2.74-9.77], p = 0.001) were the independent risk factors for the occurrence of children refractory. In conclusion, sepsis, splenomegaly, severe bleeding, DIC, andthe history of platelet transfusion are the risk factors in pediatric patients refractory platelets. ABSTRAKTransfusitrombositseringdilakukanpadapasienanak.Transfusitrombositsendirimemilikirisikoterhadappasiendanmenambahbiayaperawatan, sehinggaperludievaluasiefektifitasnya.Menilaifaktorrisikoklinisyakni sepsis, splenomegali, DIC, pendarahanberatdanriwayattransfusitrombositterhadapkejadianrefraktertrombosit.Penelitianinimerupakanpenelitiankasuskontroluntukmenilaifaktorrisikoterjadinyarefraktertrombositseperti sepsis, DIC, splenomegali, pendarahanberat, riwayattransfusitrombosit.SelamaperiodeAgustus 2010 sampai September 2011 terdapat 1403 kasustransfusi, darikeseluruhankasustersebutdiambil 86 kejadianrefrakterdan 86 non refrakter. bivariatdidapatkan sepsis [OR 5.91 (2.90-12.05)], p = 0.000], splenomegali [OR 2.82 (1.32- 6.04.12), p = 0.006] pendarahanberat [OR 8.41(4.19-16.871), p = 0.000], DIC [OR 22.96 (6.73- 78.35), p = 0.000] riwayattransfusitrombosit [OR 5.33(2.78-10.23), p = 0.000] meningkatkanrisikorefraktertrombosit. Padaanalisismultivariat sepsis (OR 2.96 [95%IK; 1.19-7.32], p = 0.019), splenomegali (OR 3.94 [IK 95%;2.21-16.00], p = 0.000), pendarahanberat (OR 3.53 [95% IK; 1.40-8.89], p = 0.008), DIC (OR 5.54 [95% IK; 1.29-22.75], p =0.021) danriwayattransfusitrombosit(OR 2.84 [95% IK; 2.74-9.77], p =0.001) merupakanfaktorrisikoindependenterjadinyarefrakterpadaanak. Sepsis, splenomegali, pendarahanberat, DIC danriwayattransfusitrombositmerupakanfaktorrisikoterjadinyarefraktertrombositpadapasienanak.